The chemically ordered glass: the limiting composition for chemical order in amorphous packings of hard-sphere mixtures - Harrowell, Peter (2011)
We consider the limits of chemical order (i.e. avoidance of solute-solute contact) in amorphous close-packed mixtures of hard spheres of two different sizes. The upper bound on the solute concentration, beyond which solute-solute contact cannot be avoided, is determined for a range of particle size ratios. Scaling the composition by this limiting value is found to collapse plots of the solute coordination and mixture energies as a function of composition for different values of size ratios onto a single master curve. A number of features of the behaviour of amorphous alloys in the vicinity of this limiting concentration are discussed.